Mechanical properties and microstructure evolution of cryogenic pre-strained 316LN stainless steel. (January 2022) - Wu, Shanshan; Xin, Jijun; Xie, Wei; Zhang, Hengcheng; Huang, Chuanjun; Wang, Wei; Zhou, Zhengrong; Zhou, Yuan; Li, Laifeng
Highlights: Mechanical properties of 316LN stainless steel with cryogenic pre-strain were studied at different temperatures (RT, 77 K and 4.2 K). The pre-strained samples stretched at cryogenic temperature obtain higher mechanical strength. The samples stretched at 77 K possess higher elongation and hardness than RT and 4.2 K, the mechanism was explained. The results are attributed to the changes in dislocation density and martensite transformation due to temperature and cryogenic pre-strain. Abstract: The 316LN stainless steel (SS) used for TF conduits in the ITER must undergo a series of pre-deformation during the fabrication. In order to investigate the variation of mechanical properties of 316LN SS with different temperature and cryogenic pre-strain, the cryogenic pre-strained samples with 0%, 15%, 25%, and 35% pre-strain were prepared and stretched at room temperature (RT), 77 K and 4.2 K, respectively. The yield strength (YS), ultimate tensile strength (UTS), elongation and microhardness of the samples were measured. Besides, the Scanning Electronic Microscopy (SEM) and Transmission Electronic Microscopy (TEM) were applied to observe the microstructure of 316LN SS. The magnetic measurements for the samples were carried out to investigate the volume percent of phase transformation. The results indicate that the YS, UTS and microhardness of 316LN SS are improved by means of cryogenic pre-strain and the decrease of elongation of pre-strained samples is different at different temperatures. All 316LN samples show the ductile fracture. The dislocation of samples promotes by cryogenic pre-strain and hinders by cryogenic temperatures. The martensitic transformation occurs after all pre-strained samples were stretched. The volume percent of α' martensite is minimal at RT and increases dramatically at cryogenic temperatures (77 K and 4.2 K). The combination of dislocation density and martensitic transformation results in changes in the 316LN SS mechanical properties.